T-cell responses induced by SARS-CoV-2 index-virus nanoparticle protein vaccine to the ancestral and omicron variants 6 months following primary vaccination - William C. McMahon; Gaurav Kwatra; Marta C. Nunes; Alane Izu; Anthonet L. Koen; Johann Greffrath; Sharon Shalekoff; Caroline T. Tiemessen; Vivek Shinde; Chijioke Bennett; Shabir A. Madhi (Communications Medicine)
Abstract Background The SARS-CoV-2 index-virus nanoparticle protein vaccine (NVX-CoV2373) induces humoral and cell-mediated immune responses that protect against severe COVID-19, including from SARS-CoV-2 variants. Limited information exists on NVX-CoV2373–induced cell-mediated immune responses to ancestral SARS-CoV-2 and the Omicron variant following a homologous booster (third dose), and on T-cell responses following a booster dose compared to a single dose. Methods T-cell responses were investigated in participants from a randomised, placebo-controlled, phase 2A/2B trial of NVX-CoV2373 in South Africa, who had a blinded crossover at 6 months post-enrolment. Peripheral blood mononuclear cells were available for 34 participants, 7 days post-vaccination with one NVX-CoV2373 dose (n = 17) or a homologous booster (n = 17). T-cell responses to the full-length spike (FLS) glycoprotein of ancestral Wuhan-Hu-1 SARS-CoV-2 and mutated spike protein regions found in Omicron (BA.4/BA.5) were characterised by intracellular cytokine staining. Results Here we show that FLS-specific T-cell responses are similar between single-dose and booster-dose recipients (CD4+: p = 0.871; CD8+: p = 0.491) and are predominantly monofunctional (IFN-γ or TNF-α). A third NVX-CoV2373 dose increases the FLS-specific polyfunctional cytokine production profile of CD4+ T cells compared with after a single dose (p = 0.045), whereas CD8+ T cells remain unaffected (p = 0.462). Only CD4+ T cells exhibit reduced reactivity to Omicron compared with ancestral SARS-CoV-2 in single-dose (p = 0.010) and in booster-dose recipients (p = 0.028). Conclusions NVX-CoV2373–induced T-cell responses to ancestral SARS-CoV-2 are comparable following vaccination with a single dose compared with a third dose administered 6 months after the second dose. Our findings suggest that an NVX-CoV2373 booster dose does not enhance T-cell immunity. Furthermore, NVX-CoV2373 vaccination induces greater T-cell response magnitudes to ancestral SARS-CoV-2, from which the vaccine is derived, compared with the Omicron variant.